Untreated herpes simplex virus encephalitis without a fatal outcome - SİLİ, ULUHAN (SPRINGER, 2021)
Herpes simplex virus encephalitis (HSE) is the most common sporadic fatal encephalitis. Although timely administered acyclovir treatment decreases mortality, neuropsychiatric sequelae is still common among survivors. Magnetic resonance imaging is frequently utilized for the diagnosis of HSE, which typically involves temporal lobe(s) and can be mixed with brain tumors involving the same area. Here, we report a case of HSE, who received acyclovir with a delay of 90 days because of presumptive tumor diagnosis and survived with minimal sequelae.
Keywords: Herpes virus; Encephalitis; Treatment